Examination of the Lemon Effect on Risk Elements Concentrations in Herbal and Fruit Teas - Yalcin Gorgulu, Tugce; Kipcak, Azmi Seyhun; Dere Ozdemir, Ozgul; Moroydor Derun, Emek; Piskin, Sabriye (CZECH ACADEMY AGRICULTURAL SCIENCES, 2014)
Fennel, mint (peppermint), and sage herbal teas and apple, lemon, and rosehip fruit teas were selected for the determination of the following risk elements contents: aluminium (Al), arsenic (As), barium (Ba), cadmium (Cd), nickel (Ni), lead (Pb), and antimony (Sb). Moreover, the effect of lemon on these elements contents was also examined. Inductively Coupled Plasma Optical Emission Spectrometry (ICP-OES) was used for these experiments on selected teas (2 g of tea infused in 100 ml of water). The maximum changes of elements concentrations after the lemon addition were as follows: Al 1077 mu g/l in lemon tea; Ba 12560 mu g/l in rosehip tea; Cd 183 mu g/l in sage tea; Ni 1136 mu g/l in fennel tea; and Pb 238 mu g/l in lemon tea. Both As and Sb were below the detection limits in pure tea and lemon-infused teas. This study indicated that after the lemon addition, rosehip tea had a hazard index (HI) value of 10827 x 10(-4) for 200 ml/day (2 cups/day), which represents a high risk for human health. If lemon is added to rosehip tea for consumption, 100 ml/day is recommended according to the calculated HI values.
Keywords: Hazardous elements; tea infusion; human health; ICP-OES; HI; MULTIELEMENT ANALYSIS; TRACE-ELEMENTS; ALUMINUM; HEALTH; LEAVES; Food Science & Technology